THE CHARACTERIZATION OF CHEMICAL, AMINO ACID AND FATTY ACID OF CATFISH (Clarias nieuhofii) GENERAL WATERAND CULTIVATION - Tri Ayu Ningsih; Rahman Karnila; Andarini Diharmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract This study was aimed to obtain the chemical compositions, amino acids and fatty acids of catfish (Clarias nieuhofii) that live in general waters and cultivation. This study using the comparative experimental with T-test consists of two treatment that was the catfish from general waters and cultivation. Data obtained served in the form of table, analyzed in descriptively and statistically with an average deviation standard of variable T1 and T2. The chemical characteristics of meat catfish of general waters and cultivation based on dry weight were water holding capacity 21.63, 19.30%, water content 83.27, 83.76%, ash content 4.64, 3.30%, fat content 2.15, 3.36%, protein content 87.29, 81.75%, carbohydrate content 5.93, 11.35%, amino acids 91.99%, 86.58%, fatty acids 81.99%, 86.62%, respectively. The fish habitat was significantly affect to water holding capacity, water, ash, fat, protein, carbohydrate, amino acids and fatty acids content.Keywords:amino acids, Clariasnieuhofii, cultivation, general waters